2018
DOI: 10.3889/oamjms.2018.129
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Facial Features of Robinow Syndrome: A Case Report

Abstract: BACKGROUND:Robinow Syndrome is an extremely rare genetic disorder characterised by abnormalities in head, face and external genitalia. This disorder exists in dominant pattern with moderate symptoms and recessive pattern with more physical and skeletal abnormalities. It was first introduced by Menihard Robinow in 1969. It was related to chromosome 9q22 ROR2 gene related to bone and cartilage growth aspects.CASE PRESENTATION:A 17-year-old Egyptian male presented to National Research Centre Orodental genetics Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A confirmatory genetic panel consisting of DVL1 , DVL3 , FZD2 , NXN , ROR2 , WNT5A , and GPC4 should be obtained if craniofacial evaluation substantiates a high suspicion for this diagnosis. Surgical management considerations include correction of midface deficiency with zygomatic augmentation, rhinoplasty to address nasal deformities, release of labial musculature, and orthodontic treatment (Mossaad, Abdelrahman, Ibrahim, & Al Ahmady, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A confirmatory genetic panel consisting of DVL1 , DVL3 , FZD2 , NXN , ROR2 , WNT5A , and GPC4 should be obtained if craniofacial evaluation substantiates a high suspicion for this diagnosis. Surgical management considerations include correction of midface deficiency with zygomatic augmentation, rhinoplasty to address nasal deformities, release of labial musculature, and orthodontic treatment (Mossaad, Abdelrahman, Ibrahim, & Al Ahmady, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…S9E, S9F), suggesting that Hh or canonical Wnt signaling signaling are not involved in tongue frenum formation. In addition to Lgr5 / Tbx22 , it has been shown that the deletion of non-canonical Wnt signaling-related molecules, Wnt5a and Ror2 , led to a lack of tongue frenum (Liu et al, 2012, Mossaad et al, 2018). We found p-c-Jun (marker of non-canonical Wnt signaling) positive cells in wild-type tongue frenum at E12, and in AP region at E11.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%